In Vivo Embryo Production in Horse: First Successful Case in Indonesia - Suryadi, W. P.; Nur’uscelawati, L.; Haq, N. M. D.; Boediono, A.; Agil, M.; Purwantara, B.; Amrozi (Tropical Animal Science Journal, 2026)
In Indonesia, equine breeding has been largely limited to natural mating and artificial insemination (AI). Embryo transfer (ET) offers a more efficient reproductive approach by enabling the production of multiple offspring per year from genetically superior mares. This study evaluated the potential of in vivo embryo production in horses in Indonesia by examining the effects of embryo collection timing, oxytocin administration, and the duration of dominant follicle development on embryo recovery rates. Donor mares were selected based on physical examination and ovarian activity. Estrous cycles were synchronized using hormonal manipulation, and the estrous period was monitored by assessing ovarian follicular development and ovulation timing. AI was performed, and embryos were collected by uterine flushing on days 5, 6, and 7 after ovulation. No embryos were recovered on day 5, suggesting that embryos had not yet entered the uterus. In contrast, collections on days 6 and 7 resulted in recovery rates of 66.7% on both days, yielding embryos at the early blastocyst and blastocyst stages, respectively. Improved outcomes were observed in mares with dominant follicle development of ≤4 days and those receiving oxytocin. However, mares with mild reproductive disorders, such as endometritis, failed to produce embryos regardless of treatment. These results indicate that successful embryo recovery in horses depends on accurate collection timing, optimal follicular dynamics, and good uterine health of donor mares.